Campylobacter Reactive Arthritis: A Systematic Review - Pope, Janet E. (2007)
OBJECTIVE: To review the literature on the epidemiology of Campylobacter associated ReA. METHODS: A Medline (PubMed) search identified studies from 1966–2006 that investigated the epidemiology of Campylobacter associated ReA. Search terms included: “reactive arthritis”, “spondyloarthropathy”, “Reiter’s syndrome”, “gastroenteritis”, “diarrhea”, “epidemiology”, “incidence”, “prevalence”, and “Campylobacter”. RESULTS: The literature available to date suggests that the incidence of Campylobacter reactive arthritis may occur in 1 to 5% of those infected. The annual incidence of ReA after Campylobacter or Shigella may be 4.3 and 1.3 respectively per 100,000. The duration of acute ReA varies considerably between reports, and the incidence and impact of chronic reactive arthritis from Campylobacter infection is virtually unknown. CONCLUSIONS: Campylobacter associated ReA incidence and prevalence varies widely from reviews such as: case ascertainment differences, exposure differences, lack of diagnostic criteria for ReA and perhaps genetics and ages of exposed individuals. At the population level it may not be associated with HLA-B27 and inflammatory back involvement is uncommon. Follow up for long-term sequelae is largely unknown. Five percent of Campylobacter ReA may be chronic or relapsing (with respect to musculoskeletal symptoms).